Antioxidant, angiotensin converting enzyme inhibitory and anthelmintic activities of bark essential oil of Cinnamomum bejolghota (Buch.-Ham.) Sweet from North East India - Gogoi, Barnali; Tamuli, Kashyap J.; Saikia, Snigdha; Lhouvum , Neipihoi; Bordoloi, Manobjyoti; Sarma, Hemanta K. (Vietnam Journal of Science and Technology, 2023)
Cinnamomum bejolghota (Buch.-Ham.) Sweetisa traditional anthelmintic and cardiotonic medicinal plant. The essential oil extracted from the bark of C. bejolghota was characterized by gas chromatography-mass spectrometry and 28 constituents were identified. Monoterpenoids were found to be dominating chemical constituents with α-terpineol (18.57 %) as the major component of the essential oil. The antioxidant activity of the essential oil was evaluated by DPPH radical, β-carotene bleaching and reducing power assay methods. The essential oil showed in-vitro dose-response hindering activity against angiotensin-converting enzyme with an IC50 value of 33.43 ± 0.46 µg/mL.The essential oil also exhibited potent anthelmintic property in-vitro against Caenorhabditis elegans with an ED50value of 80.53 ± 3.57 µg/mLin adult mortality assay. The inhibitory activity of essential oil against larval development assay showed an ED50value of 72.40 ± 2.68 µg/mL against C. elegans larva. Further, the egg hatching assay using C. eleganseggs demonstrated an ED50 value of 68.27 ± 3.51 µg/mL with this essential oil. Thus, the ethnomedicinal claim has been validated for the bark essential oil, which provides an excellent scope for the development of the C. bejolghota bark essential oil as novel herbal antihypertensive and anthelmintic agents.